Caste differences in the association between dopamine and reproduction in the bumble bee Bombus ignitus. (November 2017) - Sasaki, Ken; Matsuyama, Hinako; Morita, Naruaki; Ono, Masato
Graphical abstract: Highlights: Colony founding queens had depressed dopamine levels in the brains. Brain dopamine levels were correlated with other ganglia and hemolymph in queens. In virgin queens, dopamine levels were not correlated with ovarian activity. In workers, dopamine levels were positively correlated with ovarian activity. Dopamine may play a role in ovarian activity in workers, but not in queens. Abstract: A society of bumble bees is primitively eusocial, with an annual life cycle, and can be used as a physiological model of social bees for comparative studies with highly eusocial hymenopterans. We investigated the dynamics of biogenic amine levels in the brain, meso-metathoracic ganglia, terminal abdominal ganglion, and hemolymph in queens 1 day after mating (1DAM), during diapause (Dp), and during colony founding (CF) in the bumble bee, Bombus ignitus . Dopamine levels in the brain of CF queens were significantly lower than in 1DAM and Dp queens, and the levels in the thoracic ganglia and hemolymph in CF queens were lower than in 1DAM queens, but did not differ from other groups in the abdominal ganglion. Octopamine levels in the brains were higher in Dp queens than in 1DAM queens. Serotonin and tyramine levels did not differ between the groups in different compartments of the central nervous system (CNS) that we examined. The dopamine levels in the brains were significantly positively correlated with those in the thoracic ganglia, abdominal ganglion, and hemolymph, suggesting the regulation of dopamine levels among three different compartments of the CNS. In isolated virgin queens, there were no significant correlations between the brain levels of biogenic amines that we examined and the lengths of the largest terminal oocytes, whereas, in isolated workers, the brain dopamine levels were positively correlated with oocyte lengths. These results suggest that dopamine is associated with ovarian activity in reproductive workers, but not in either virgin or mated queens.